A Framework for the Sustainable Control and Optimization of Resources in Agriculture - Pereira, Fernando Lobo; Pena, Ismael [UNESP]; Silva, Geraldo Nunes [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This article concerns the issue of optimizing strategies of resources management in Agriculture. The increasing human population, and the anthropogenic environmental impacts resulting from the current agricultural food production practice raise tremendous challenges as the latter constitutes a huge threat to the overarching goal of eliminating hunger from the Earth's face. The contribution of this article consists in showing the stability and convergence of a bi-level optimization based control architecture to de-conflict the short-term profit-seeking goals of each agricultural production unit with the long-term goal of attaining the collective environmental equilibrium required to preserve the necessary food production efficiency level. Given the complexity of any realistic scenario, we consider a very simple context clarifying the core mathematical issues of a bi-level control architecture previously proposed by the authors that, under reasonable assumptions, generates control strategies ensuring the asymptotic convergence to an environmentally healthy equilibrium while ensuring the economic (and, thus, social) short term sustainability.